2017
DOI: 10.1038/s41598-017-08552-3
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite evidence of dispersal mechanism of red swamp crayfish (Procambarus clarkii) in the Pearl River basin and implications for its management

Abstract: Discerning the dispersal patterns of invasive species is critically important for the design of effective management strategies and the development of appropriate theoretical models predicting the spatial expansion of introduced populations. Post-introduction dispersal may occur naturally or via human transport, but for many organisms, assessing the relative contribution of each of these factors is difficult using traditional methods. Here, we explored the genetic patterns associated with the spread of red swa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
(58 reference statements)
1
8
0
1
Order By: Relevance
“…Considering that the HX population was farthest from the other populations, the result excluding Hengxian was also significant (R 2 = 0.4916, p = 0.0167 *). Similar phylogeographic divergence has been reported in other aquatic organisms (i.e., red swamp crayfish and darters) in the Pearl River basin [79,80]. The IBD pattern also agrees well with the life history of this species.…”
Section: Population Structure and Habitat Fragmentationsupporting
confidence: 85%
“…Considering that the HX population was farthest from the other populations, the result excluding Hengxian was also significant (R 2 = 0.4916, p = 0.0167 *). Similar phylogeographic divergence has been reported in other aquatic organisms (i.e., red swamp crayfish and darters) in the Pearl River basin [79,80]. The IBD pattern also agrees well with the life history of this species.…”
Section: Population Structure and Habitat Fragmentationsupporting
confidence: 85%
“…We further speculate that the colonization of the marsh of Mès probably resulted from a secondary introduction event using an inoculum from the marsh of Brière given that the allelic composition of the network of Mès was nested in that of the marsh of Brière. Comparable variations in the levels of genetic diversity between waterbodies were found elsewhere (Huang et al, 2017;Li et al, 2012;Paulson & Martin, 2014;Yi et al, 2018), but such a fine genetic signal of crayfish spread was not identified, probably blurred by multiple introduction events at several locations and/or recurrent gene flow between populations after crayfish was introduced.…”
Section: Pattern Of Range Expansion and Current Levels Of Gene Flowmentioning
confidence: 76%
“…The species acclimatizes to a wide range of aquatic environments, and generally spreads rapidly once introduced (e.g., Capinha, Brotons, & Anastácio, ; Lodge et al, ). Recent studies have investigated the genetic structure of populations of the red swamp crayfish at large spatial scales, and highlighted the predominant role of anthropogenic dispersal in its spread across regions (Huang, Tang, Cai, Lin, & Wu, ; Yi et al, ). Tracking studies have also revealed its capacity to travel several kilometres (Aquiloni, Ilhéu, & Gherardi, ; Barbaresi, Santini, Tricarico, & Gherardi, ; Gherardi & Barbaresi, ; Gherardi, Tricarico, & Ilhéu, ), and to resist desiccation well enough to cross terrestrial habitats (Banha & Anastácio, ; Ramalho & Anastácio, ).…”
Section: Introductionmentioning
confidence: 99%
“…As a model organism, P. clarkii is not only used to investigate invasive routes and dispersal patterns [11,18], but also to perform research on animal behavior [19][20][21] and environmental stress and toxicity [22][23][24][25]. With the rapid development of the aquaculture industry, P. clarkii is often infected by various pathogens such as bacteria, viruses, and spiroplasmas [26][27][28][29], resulting in severe decreases in P. clarkii production.…”
Section: Introductionmentioning
confidence: 99%